Clinical Performance of the Aspergillus Western Blot IgG Kit for Serodiagnosis of Chronic Pulmonary Aspergillosis in Post-Tuberculosis Patients - Sresta Azahra; Findra Setianingrum; Heri Wibowo; Anna Rozaliyani (Jurnal Respirologi Indonesia, 2023)
Background: Chronic pulmonary aspergillosis (CPA) by Aspergillus spp., which causes slowly progressive destruction to lung parenchyma, is a major complication of pulmonary tuberculosis (TB). Clinical and radiological features of CPA are not typical and might resemble TB. Therefore, detecting Aspergillus-specific IgG is critical for diagnosing CPA.Methods: This cross-sectional study was conducted to evaluate the performance of Aspergillus Western Blot (Asp-WB) IgG kit (LDBio Diagnostics, Lyon, France) for CPA diagnosis in 63 post-TB patients. The analysis was performed by comparing Asp-WB with Aspergillus ELISA IgG (Asp-ELISA) and fungal culture as standard method.Results: Of the 63 patients studied, twenty six (41%) met the probable CPA criteria. The Asp-WB results were positive in 13 probable CPA patients and 3 non-CPA patients, with the significant difference of 50% vs. 8% (p< 0.001). The sensitivity and specificity of Asp-WB were 50% and 93%. False negative results of Asp-WB were detected from non-fumigatus CPA that grew Aspergillus niger. CPA patients with mild symptoms (less than 3 months) indicated early progression of CPA might showed positive Asp-WB test result in low sensitivity of Asp-WB test.Conclusion: The Asp-WB has potential to use as confirmatory test to assist diagnosis of CPA in post-TB patients.